Improved Construction of Auricular Prosthesis by Digital Technologies. Issue 6 (September 2015) - Nuseir, Amjad; Hatamleh, Muhanad; Watson, Jason; Al-Wahadni, Ahed M.; Alzoubi, Firas; Murad, Mohammed
Abstract : Abstract: Implant-retained auricular prostheses are a successful prosthetic treatment option for patients who are missing their ear(s) due to trauma, oncology, or birth defects. The prosthetic ear is aesthetically pleasing, composed of natural looking anatomical contours, shape, and texture along with good color that blends with surrounding existing skin. These outcomes can be optimized by the integration of digital technologies in the construction process. This report describes a sequential process of reconstructing a missing left ear by digital technologies. Two implants were planned for placement in the left mastoid region utilizing specialist biomedical software (Materialise, Belgium). The implant positions were determined underneath the thickest portion (of anti-helix area) left ear that is virtually simulated by means of mirror imaging of the right ear. A surgical stent recording the implant positions was constructed and used in implant fixtures placement. Implants were left for eight weeks, after which they were loaded with abutments and an irreversible silicone impression was taken to record their positions. The right existing ear was virtually segmented using the patient CT scan and then mirror imaged to produce a left ear, which was then printed using 3D printer (Z Corp, USA). The left ear was then duplicated in wax which was fitted over the defect side. Then, it was conventionally flasked. Skin color was digitalized using spectromatch skin color system (London, UK). The resultant silicone color was mixed as prescribed and then packed into the mold. The silicone was cured conventionally. Ear was trimmed and fitted and there was no need for any extrinsic coloring. The prosthetic ear was an exact match to the existing right ear in shape, skin color, and orientation due to the great advantages of technologies employed. Additionally, these technologies saved time and provided a base for reproducible results regardless of operator.